Sustainable use of geothermal resources - Ramos De La Cruz, John (2016)
This article discusses the use of geothermal resources as a new energy source, which has a demonstrated technical and economic feasibilityIn our country, we have incipient regulations, which in many cases and due to lack of regulations and specialists in the field, take a lengthy period of time to obtain authorizations and / or concessions for the exploitation of geothermal resources of the soil and subsoil in our nation’s territory.Under the current Peruvian legal system, the authorizations are granted for a period of three (3) years and may be extended for an additional period of two (2) years; in the case of concessions they are granted for a period of thirty (30) years and may be extended for an additional period of ten (10) years.If the goal is the generation of electricity, the contract will be automatically extended for the same term of the contract. Notwithstanding this, it should be specified that the power generation activities are governed by their ow